Modal Analysis Study On Aluminum 6061 Using Accelerometer And Piezoelectric Film Sensor - Ramli, Mohd Irman; Nuawi, Mohd. Zaki; Mohammad Rasani, Mohammad Rasidi; Abdullah, Shahrum; Kho, Ko Seng (Research India Publications, 2017)
This study is conducted to determine vibration or modal parameters such as natural frequencies and mode shapes of aluminum 6061 (Al6061). If the component vibrates with frequency coherence with the natural frequency, resonance frequency will occur and structural failure might emerge. Modal analysis study is conducted by both simulation and experimental methods. Simulation is conducted via ANSYS software while impact hammer testing is done for experimental work to determine the vibration parameter. Two sensors are used, which are piezoelectric film and accelerometer. Hence, the results obtained from accelerometer showed that frequencies for mode shape 1, 2, 3, 4, 5 and 6 for rectangular shape are 272.00Hz, 521.33Hz, 913.00Hz, 1080.67Hz, 1437.33Hz and 1803.00Hz. The results obtained from piezoelectric film showed that frequencies for mode shape 1, 2, 3, 4, 5 and 6 for rectangular shape are 258.33Hz, 524.67Hz, 884.33Hz, 1141.67Hz, 1399.67Hz and 1752.33Hz. Finally, the results captured from simulation appeared that frequencies for mode shape 1, 2, 3, 4, 5 and 6 for rectangular shape are 291.72Hz, 647.63Hz, 841.42Hz, 1465.00Hz, 1554.00Hz and 1952.40H respectively. The results showed that low cost sensor which is piezoelectric film proved to be reliable in detecting the modal parameter.